MENAKAR PELUANG OPTIMALISASI PENDIDIKAN KARAKTER MELALUI KERJASAMA LEMBAGA FORMAL DENGAN MADRASAH DINIYAH - Sabiq, Fikri (Universitas Nurul Jadid, 2020)
This study aims to formulate the concept of cooperation between Madrasah Diniyah which has religious character education but is less attractive to the public with formal education that is of interest to the community but lacks character education. This research is a literature study with the primary source being Presidential Decree Number 87 of 2017. While the secondary sources are various local regulations issued by the Regent or Mayor regarding Madrasah Diniyah. The forms of cooperation opportunities that exist between Madin and formal education can include several aspects. First, the curriculum aspect, where the two institutions can complement and complement each other. Second, the legality of the program where formal institutions can oblige students to study at Madin. Third, the social aspect in which these institutions can work together with community leaders so that they can support each other so that these formal and non-formal institutions can provide wider benefits. This cooperation can be maximized if it gets support from local officials, the Ministry of Religion, and the Education Office.